Penyelesaian Cerai Gugat Secara Verstek Pada Putusan Nomor 270/Pdt.G/2020/PA.Sak di Pengadilan Agama Siak Sri Indrapura - Rahmi Febriani; Mardalena Hanifah; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Based on the legal system in Indonesia, the divorce process must be carried out by way of alawsuit in court, where the judge will act as a mouthpiece for the husband and wife who are inlitigation so that they can give a decision which is expected to be the best solution. One of thedivorce cases that need to be highlighted is a divorce that occurs after a verstek decision from thecourt. This decision is a decision issued by a judge when one of the parties (the Defendant) ortheir attorney never comes to attend the trial. There is one verstek lawsuit divorce decision that thewriter will examine in this research, namely the decision of the Siak Sri Indrapura Religious CourtNumber 270/Pdt.G/2020/PA.Sak. In their verdict, the panel of judges granted the plaintiff's claimby giving a verstek unseen verdict. This study aims to determine the extent to which the decision isable to provide justice for the litigants, and review whether the considerations of the panel ofjudges in deciding are in accordance with the applicable laws and regulations.The type of this research is sociological legal research, namely legal research conducted by directresearch into the field plus legal literature or secondary data. This research will further examinethe various sources of law in the form of applicable laws or regulations related to the theory ofjustice and the theory of judge's decision in the divorce process where the decision is in the formof an unseen ruling in a verstek way.The data collection technique in this study was the review ofwritten information (library research). After the data was collected, it was analyzed to drawconclusions.From the research results, there are two main things that can be concluded. First, the strength ofthe witnesses in case Number 270/Pdt.G/2020/PA.Sak has fulfilled the requirements based onstatutory regulations but is not strong because the witness has an emotional bond with thePlaintiff. Second, the settlement in this contested divorce was carried out with the issuance of averstek decision because neither the Defendant nor his attorney was present before the trial.Keywords: Settlement–Divorce Lawsuit–Verstek–Religious Court